AYURVEDIC APPROACH FOR ASCITES: A CASE STUDY - Jain, Ankita Pravin; Chandurkar, Vivek S. (International Journal of Research -GRANTHAALAYAH, 2018)
A 49yrs male patient presenting with udarvriddhi (abdominal distention), dourbalya (gen. weakness), ubhaypadshoth (bilateral pedal edema) diagnosed as Udarvyadhi (ascites) was brought to SSNJ Ayurved Hospital, Solapur.Patient was treated with an integrated approach of ayurveda. According to ayurveda, treatment of is nityavirechana (purgative), agnideepan (increase appetite), balaprapti (stimulant for hepatic function), lepachikitsa, Proper diet (cow milk) and external application of arkapattabandhan (belt made by leaves of Calotropisprocera). Appreciable results were observed in the form of reduction in abdominal girth, decreased pedal edema, increased appetite, increased strength and significant changes in investigations.